2015
DOI: 10.31018/jans.v7i2.663
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of lead in the muscle of brackish water fish (Boleopthalmus dussumieri)

Abstract: Lead is highly toxic, impairing biological functions of aquatic animals. In vitro, static test was performed to find out the accumulation of lead in the muscle of brackish water fish (Boleopthalmus dussumieri). Fish were maintained in experimental aquaria with lead nitrate solution having known lead concentration of 1.48 and 14.8 mg/l, respectively. The experiments were performed in triplicate. Two fishes from each exposed aquarium were sampled on zero hour, 96 hours and 192 hours. Muscle was removed and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This decline may be related to the negative impact of Pb toxicity on the various metabolic processes. According to Bengani et al (2015), Pb is a toxic element that impairs biological functions. Ikeogu et al (2016) hypothesized that fish exposed to Pb toxicity experienced slow growth and high mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…This decline may be related to the negative impact of Pb toxicity on the various metabolic processes. According to Bengani et al (2015), Pb is a toxic element that impairs biological functions. Ikeogu et al (2016) hypothesized that fish exposed to Pb toxicity experienced slow growth and high mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between lead concentrations in the water and sediment can provide information about potential sources and transport mechanisms of lead in the study area. However, the absorption and accumulation of lead in fish can be influenced by various factors, such as species, feeding habits, and exposure routes [ 70 ], with the food pathway being more significant in some cases [ 71 , 72 ]. For factors such as transfer and bioaccumulation, elements like Zn and Cu had the highest proportions and interactions with rainbow trout in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in growth may also be attributed to the effect of the heavy metal on enzyme activities and metabolic processes. Bengani et al, (2015) reported that Pb is highly toxic, impairing the biological functions of aquatic animals. Rani and Gupta (2015) reported that water pollution with heavy metals affects various physiological processes in fish including poor food utilization and reduced fish metabolic rate.…”
Section: Discussionmentioning
confidence: 99%